Exploring the Attitudes of Students to Distance Learning during Covid-19 in Morocco: The Case of Students of English Studies at Faculty of Letters in Beni-Mellal - Said Elmouhtarim (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2021)
Accompanying the outbreak of Covid-19 pandemic, there has been an unprecedented practice in education worldwide. This was resorting to distance learning (DL) at large. Morocco is no exception. Having continued our teaching practice through this new orientation in the second semester of the academic year 2019-2020, we thought that this experience is worth reflecting about. This study which aims at exploring the attitudes of the students to distance learning. The methods of this research is quantitative study where questionnaire administered to a target population of 160 students belonging to the department of English studies at Faculty of Letters in Beni-Mellal, Morocco. The findings we obtained from a questionnaire addressed to 160 students at the Faculty of Letters in Beni-Mellal revealed that the attitudes of students towards distance learning are generally speaking positive. Still, it must be admitted that these findings also showed that there are some challenges facing a sound implementation of this new orientation in teaching, which necessitates some requirements both in terms of digital resources and digital pedagogy to reach efficiency in the future.